KEPEMIMPINAN MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN PRODUKTIVITAS KERJA GURU DI SMA NEGERI 1 RASAU JAYA - Safitri, Maika Wida; Asrori, M. (Universitas Tanjungpura, 2021)
AbstractThis study aims to reveal Principal Managerial in increasing Teacher Work Productivity at State Senior High School 1 Rasau Jaya which includes: planning, organizing, motivating, and rewarding. The study used a descriptive approach. The research subjects were the Principal, Vice Principal of Curriculum, Vice Principal of Student Affairs, Head of Libraries, and Teachers. All subjects are teachers who teach at State Senior High School 1 Rasau Jaya. Data collection methods used interviews, documentation, and observation. The data analysis model uses data reduction, data presentation, and conclusions. Test the validity of the data using trials and triangulation. The results of the study show the following: 1) Planning can be done through identifying what will be programmed, how it will be programmed, who will be involved, when it will be implemented, and how it will be implemented. The product of the planning is in the form of a School Activity Plan 2) This organization is carried out by division, principal and function equipped with an explanation of the duties of each teacher, 3) Motivating is carried out verbally and non-verbally continuously with Target and self-evaluation techniques Progress, Expectation of results, and Social comparisons and 4) Rewards are carried out with techniques that maintain a conducive working atmosphere.Â Keywords: Leadership, Managerial, Work Productivity